Assessing the Effectiveness of Peer-Mentoring Programs on Academic Persistence and Dropout Rates in Vocational High Schools - Sisca Septiani; Wiwik Hidayati; Ibrahim Youssef Farahat Ismail (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the impact of peer-mentoring programs on vocational high school (SMK) students, focusing on academic resilience, dropout rates, and overall academic performance. The research compares the outcomes of students in schools with and without peer-mentoring programs. The findings indicate that students participating in peer mentoring exhibited significantly lower dropout rates (12%) compared to those in the control group (22%). Additionally, the continuation rate for students in the experimental group was higher (88%) than in the control group (78%). Academic performance was also positively affected, with an average score of 75 for the experimental group, compared to 65 for the control group. Statistical analysis confirmed the significance of these differences, highlighting the positive effects of peer-mentoring programs. The study suggests that peer mentoring not only enhances academic performance but also contributes to improved student retention by providing emotional and social support. The results underscore the importance of well-structured mentoring programs, including effective mentor training and proper matching between mentors and mentees, to maximize the benefits for vocational students.